Post Dakwah di Era Cyber Culture - Harry Purwanto; Achmad Arifulin Nuha (Institut Agama Islam Syarifuddin Lumajang, 2020)
The development of technology has a big influence in all aspects of life, including in da'wah. Preachers face the challenges in the era of cyber culture, where information flow and cultural development are connected with the digital space. This article discusses the relationship between da'wah and cyber culture. Accompanied by any challenges that must be faced by preachers, as well as how the right strategy to convey Islamic teachings in the current era. In another section, also stated what is called the Post Da'wah. This concept refers to the facts that have happened lately. Da'wah which initially has values ​​of the sacredity of values ​​that upholds a truth of the state is then distorted by profane values. In fact, the new technology also supports pseudo reality in da'wah. Then, da’wah becomes a tool of manipulation in order to achieve economic benefits, bodily sexism, which is displayed through symbolic visualization. Da'wah is trapped in the world of imagery. Not only that propaganda, later became a political propaganda tool to seize power and maintain power. Interest takes precedence without regard to reason. These facts are referred to as Post Da'wah. Keywords: Da'wah, Cyber, Culture, Strategy, Technology